2021
DOI: 10.1101/2021.12.10.21267477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes Associated with Expanded Take-Home Eligibility for Outpatient Treatment with Medications for Opioid Use Disorder: A Mixed-Methods Analysis

Abstract: BackgroundAccess to medications for opioid use disorder (MOUD) in the U.S. is highly restricted. In March 2020, to reduce transmission of COVID-19, SAMHSA issued emergency regulations allowing up to two weeks of take-home doses for most patients.ObjectivesWe evaluated the benefits and unintended consequences of these new regulations expanding take-home eligibility to inform MOUD policy post-pandemicMethodsWe conducted a mixed-methods evaluation of an opioid treatment program in San Francisco caring for a diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Trietler et al’s study among a small group of New Jersey MOUD providers reported a shift towards telehealth, a reduction in toxicology screening and counseling services, and modifications to multi-day dosing [ 38 ]. A study of a San Francisco methadone treatment program reported full implementation of federal regulations (largely undefined) with outcomes demonstrating the benefit of increased take-home doses on hospitalizations and emergency department visits [ 39 ]. The closest alignment of provider reporting and patient experience is a multi-state study by Krawczyk of unpublished data reported to HHS Office of The Inspector General from methadone clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Trietler et al’s study among a small group of New Jersey MOUD providers reported a shift towards telehealth, a reduction in toxicology screening and counseling services, and modifications to multi-day dosing [ 38 ]. A study of a San Francisco methadone treatment program reported full implementation of federal regulations (largely undefined) with outcomes demonstrating the benefit of increased take-home doses on hospitalizations and emergency department visits [ 39 ]. The closest alignment of provider reporting and patient experience is a multi-state study by Krawczyk of unpublished data reported to HHS Office of The Inspector General from methadone clinics.…”
Section: Discussionmentioning
confidence: 99%